Dominoes, danzón, and death [large type] - Reyes, Raquel V. (Caribbean kitchen mystery, 2025)
Latina sleuth and culinary master Miriam Quįones-Smith is cooking up a storm in the fourth installment of the Caribbean Kitchen mystery series. It's been three years since food anthropologist and cooking show star Miriam Quįones-Smith had her last brush with death. Her Spanglish culinary show, Abuela Approved, is topping the charts. Her parents are back in Miami and living with her in Coral Shores. And her kids are great. But when bones start popping up in unexpected places, Miriam's idyllic life is threatened. Her husband Robert's much-delayed hotel project screeches to a halt when human bones are unearthed. Tribal representatives, forensic archaeologists, and a pompous professor rain down on the possibly ancient site. Then a fake skeleton with the name "Smith" etched into it is found floating in the bay with an ominous note. Is it a threat to Miriam's husband or her inlaws? And when Miriam's boss Delvis is seen going off on a tour guide who marched through the crew-only area on set and is later found dead, Delvis is declared the main suspect. To protect her family and friends, Miriam must dig up the truth that has been hiding in plain sight.